KONOTATIF CIGULU-CIGULU DALAM BAHASA MELAYU MANADO (BMM) - Rawung, Willem Hanny; Kalangi, Leika M V.; Pamantung, Rina (Universitas Sam Ratulangi, 2019)
AbstractCigulu-cigulu is a form of a riddle game. A question or a statement was delivered and then the other person or the interlocuters must find the appropiate answer or the respond for the said question or statement. Cigulu-cigulu is the abbreviated form of